Sahel Droughts Induced by Large Volcanic Eruptions Over the Last Millennium in PMIP4/Past1000 Simulations. Issue 5 (2nd March 2023) - Villamayor, J.; Khodri, M.; Fang, S.‐W.; Jungclaus, J. H.; Timmreck, C.; Zanchettin, D.
Abstract: This work provides evidence of the influence of large volcanic eruptions on Sahel rainfall relying on PMIP4/past1000 multi‐model simulations, covering the last millennium. A classification of volcanic eruptions in the last millennium according to the meridional symmetry of the associated radiative forcing reveals different mechanisms of the West African Monsoon response at inter‐annual timescale. In all cases, these simulated changes result in Sahel drying up to 2 years after an eruption. Besides, we add evidence of a role of varying volcanic activity across the past millennium in the Sahel precipitation variability at multi‐decadal to secular timescales. Plain Language Summary: Relying on climate simulations of the past millennium, this work shows that the largest volcanic eruptions documented induce different mechanisms in the West African Monsoon response depending on whether the eruption occurs at extra‐tropical or tropical latitudes. In both cases, such volcanic impacts can induce droughts the two following rainy seasons in the West African Sahel region. Moreover, we show first evidence of an influence of the frequency of volcanic eruptions on the Sahel precipitation regime over decades to centuries across the past millennium. Key Points: Climate model simulations of the past millennium show Sahel drought in response to large volcanic eruptions up to the following 2 years The mechanisms leading to the Sahel drying are different if it responds to extra‐tropical or tropical eruptions The increasing frequency of eruptions throughout the past millennium modulates Sahel precipitation variability on multi‐decadal timescales